TECHNO-ECONOMIC ASSESMENT OF REPLACING DIESEL POWER PLANTS WITH OFF-GRID SOLAR PHOTOVOLTAIC SYSTEMS IN REMOTE ELECTRIFIED VILLAGES: A CASE STUDY OF GUNUNG PUREI, INDONESIA - Gustiyadi Fathur Rahmandi; Atok Setiyawan; Hendro Nurhadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The electrification of remote and isolated areas remains a major challenge in Indonesia, particularly in 3T (Outermost, Frontier, and Disadvantaged) regions that still rely on diesel power plants with limited operating hours. This study evaluates the technical and economic feasibility of replacing an existing diesel power plant (PLTD) with an off-grid solar photovoltaic (PV) system integrated with battery energy storage at the Gunung Purei Village Electricity Unit (ULD), Central Kalimantan.The proposed system is designed to transform a 14-hour diesel-based operation into a continuous 24-hour electricity supply. Technical analysis was conducted using PVsyst to assess energy production and performance ratio (PR), while economic feasibility was evaluated using HOMER Pro through indicators such as Net Present Value (NPV), Levelized Cost of Energy (LCOE), Profitability Index (PI), and Discounted Payback Period (DPP). The study compares monocrystalline and polycrystalline PV modules under different battery autonomy scenarios.Results show that the optimal configuration consists of a 588 kWp off-grid solar PV system using 940 monocrystalline PV modules, five 100 kW inverters, a 500 kW power conversion system, and 27 battery sets with a total capacity of 2.94 MWh (one-day autonomy). This configuration achieves a performance ratio of 34.78% and satisfies the annual load demand of 896.19 MWh. From an economic perspective, the system is feasible, yielding a positive NPV of IDR 8.36 billion, a PI of 1.30, and a DPP of 24.77 years.The findings confirm that off-grid solar PV–battery systems using monocrystalline modules provide a technically reliable and economically viable solution for replacing diesel generation in remote electrified villages, while supporting Indonesia’s renewable energy mix target of 23%.